PENGARUH MODEL POE PADA MATERI KOLOID TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Ratih Yuliasih; Husna Amalya Melati; Rahmat Rasmawan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
Abstract The purposes of this research were to know the difference between the critical thinking skills of the students of class XI MAN 1 Pontianak which is taught using predict-observe-explain (POE) learning and is taught using conventional model and know the influence of predict-observe-explain (POE) learning model on students' critical thinking skills on colloid subjects. The form of this research is Quasi Experiment with research design "Pretest-Posttest Control Group Design". The sample of this research is the students of class XI IPA 1 as the experimental class and XI IPA 2 as the control class. The measurement technique was used is technique of data collection.. The data collecting tool of this research is critical thinking skills test in the form of essay. Statistical test result using U Mann-Whitney test with α = 0,05 obtained value Z = -4,713 with Asymp. Sig. (2-tailed) = 0,000 located at the acceptance area. This shows that there is a significant difference between the critical thinking skills  of the students of class XI IPA MAN 1 Pontianak taught using predict-observe-explain (POE) learning and taught using conventional model on colloid subjects. The effect of POE learning model obtained percentage of 30,23 % calculated using effect size.  Keywords: POE Model, Critical Thinking Skills, Colloid